2020
DOI: 10.1186/s12886-020-01640-5
|View full text |Cite
|
Sign up to set email alerts
|

Choroidal vascular changes in retinitis pigmentosa patients detected by optical coherence tomography angiography

Abstract: Background To evaluate choroidal vascular changes, including choriocapillaris (CC) and middle/large choroidal vessels, in retinitis pigmentosa (RP) patients using wide-angle optical coherence tomography angiography (OCTA) and to determine whether changes in the choroidal vascularity have a relationship with visual function and retinal structural changes. Methods 34 patients with a confirmed diagnosis of RP and 48 controls were recruited. All patients underwent detailed ophthalmologic and imaging examinations… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
21
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 25 publications
(23 citation statements)
references
References 23 publications
(34 reference statements)
1
21
1
Order By: Relevance
“…3D CVV and CVI analyses are the highlights of our study. Previously, CVI was used to quantify choroid blood perfusion in central serous chorioretinopathy ( Yang et al, 2020 ), Stargardt disease ( Ratra et al, 2018 ), and retinitis pigmentosa ( Shen et al, 2020 ). Notably, the majority of these investigations applied a binarization algorithm to calculate the CVI.…”
Section: Discussionmentioning
confidence: 99%
“…3D CVV and CVI analyses are the highlights of our study. Previously, CVI was used to quantify choroid blood perfusion in central serous chorioretinopathy ( Yang et al, 2020 ), Stargardt disease ( Ratra et al, 2018 ), and retinitis pigmentosa ( Shen et al, 2020 ). Notably, the majority of these investigations applied a binarization algorithm to calculate the CVI.…”
Section: Discussionmentioning
confidence: 99%
“…However, in an OCT-based study of myopia in Chinese youth, the mean subfoveal Cht was 303.08 ± 76.87 μm [ 11 ], and it could be distinguished from the OCT image that it resulted from atrophy of the choriocapillaris layer. Prior research also demonstrated that the choroidal vascularity index, which reflects middle and large choroidal vascularity, has recently shown a downward trend in PR eyes [ 12 ]. In OCTA, the foveal avascular zone of the patient’s eyes were 0.334 and 0.224, respectively, and the superior vessel density was 51.2 and 51.6%, respectively, which were similar to the results reported in previous studies [ 13 ].…”
Section: Discussionmentioning
confidence: 99%
“…In the progression of retinal degeneration, the thinning of the retinal vessels causes microvascular abnormalities and BF impairment to occur in the retina and fluorescein angiography shows choroidal vascular atrophy [19]. Some RP patients even have blood circulation disorders of the body with slower cold-induced maximal flow reduction and longer warm recovery time than non-RP patients [20].…”
Section: Discussionmentioning
confidence: 99%